An Unbelievable Foreign Body in a Maxillary Sinus - Alireza Ehsanbakhsh; Nasrin Khorashadizadeh; Amin Saburi (Baqiyatallah University of Medical Sciences, 2016)
Introduction: Misdiagnosis and the resulting mismanagement are challenging issues in complicated cases which present with obscure complaints. Interpreting radiologic studies, especially conventional plain radiologic images, remains the most frequently prescribed and useful modality for the first step of assessment. Case Presentation: In this report, we present a case of mismanagement of a strange foreign body in the maxillary sinus of a child not found in a facial x-ray. Conclusion: Inexperienced non-radiologist physicians may make misdiagnoses when reading conventional x-rays.